2017
DOI: 10.1073/pnas.1620935114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cross-correlations between entangled biofilaments as they diffuse

Abstract: Entanglement in polymer and biological physics involves a state in which linear interthreaded macromolecules in isotropic liquids diffuse in a spatially anisotropic manner beyond a characteristic mesoscopic time and length scale (tube diameter). The physical reason is that linear macromolecules become transiently localized in directions transverse to their backbone but diffuse with relative ease parallel to it. Within the resulting broad spectrum of relaxation times there is an extended period before the longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Thus, we observed that the interplay between two subdiffusion mechanisms (geometrical restrictions and memory effects) may lead to the usual Brownian motion. This crossover and its physical explanation also appear consistent with experimental results of anisotropic diffusion of entangled biofilaments [84] and the mobility of water molecules on protein surfaces [85]. On the other hand, when an exponential memory kernel acts on the backbone, we obtained a crossover from subdiffusion to confined diffusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, we observed that the interplay between two subdiffusion mechanisms (geometrical restrictions and memory effects) may lead to the usual Brownian motion. This crossover and its physical explanation also appear consistent with experimental results of anisotropic diffusion of entangled biofilaments [84] and the mobility of water molecules on protein surfaces [85]. On the other hand, when an exponential memory kernel acts on the backbone, we obtained a crossover from subdiffusion to confined diffusion.…”
Section: Discussionsupporting
confidence: 89%
“…This interpretation is somehow in agreement with the results on anisotropic diffusion of entangled biofilaments reported in Ref. [84], where the authors have written:…”
Section: Generalized Comb-models With Fractional Operatorssupporting
confidence: 93%
“…Next, we consider the cross-correlations between crosslinks. Hydrodynamic arguments for a continuum anticipates C rr r 0 to be constant regardless of separation 13,17 , whereas our data is massively scattered (Fig. 4e) with negative points highlighted by the pink background.…”
Section: Discussionmentioning
confidence: 65%
“…A protocol was designed to polymerize the filaments and to fluorescently label the crosslinks by exploiting the fragmentation/fusion nature of actin filaments (Fig. 1b, see Methods section for details) 16,17 . The resulting network is composed of a “sea” of unlabeled filaments and a few labeled ones (ratio ~1000:1), in which green segments with biotin are most likely to be crosslinked to unlabeled filaments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…"With those instrumental capabilities, it became very natural to look not just at interfaces, but also at bulk mobility, the dynamics of how molecules move from point to point in space in crowded environments, and what are the mechanisms," he says. For example, Granick and his colleagues used single-molecule fluorescence imaging to elucidate correlations between neighboring actin biofilaments and colloids rather than take the conventional mean-field approach (7,8).…”
Section: Thinking Like a Moleculementioning
confidence: 99%